1998
DOI: 10.3109/15563659809162616
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-Controlled Trial of 2,3-Dimercaptosuccinic Acid in Therapy of Chronic Arsenicosis Due to Drinking Arsenic-Contaminated Subsoil Water

Abstract: Under the conditions of this study, 2,3-dimercaptosuccinic acid was not effective in producing any clinical or biochemical benefit or any histopathological improvement of skin lesions in patients with chronic arsenicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…The arsenic issue is perhaps the most distinct in Bangladesh and West Bengal, as millions of handpumped tube wells yield drinking water with arsenic concentrations above 10 μg L -1 , which is the World Health Organization drinking water guideline (18)(19)(20). In West Bengal, India, arsenic concentrations in some tube wells go as high as 3400 μg L -1 (21). This study has investigated the effects of arsenic on biochemical parameters indicative of changes in haeme biosynthesis, liver and kidney oxidative stress, and liver damage, and has investigated the ability of …”
Section: Discussionmentioning
confidence: 99%
“…The arsenic issue is perhaps the most distinct in Bangladesh and West Bengal, as millions of handpumped tube wells yield drinking water with arsenic concentrations above 10 μg L -1 , which is the World Health Organization drinking water guideline (18)(19)(20). In West Bengal, India, arsenic concentrations in some tube wells go as high as 3400 μg L -1 (21). This study has investigated the effects of arsenic on biochemical parameters indicative of changes in haeme biosynthesis, liver and kidney oxidative stress, and liver damage, and has investigated the ability of …”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effect of the dithiols is attributed to the ability of their vicinal thiol groups to react with trivalent arsenicals forming a saturated five-member heterocyclic ring [25,26]. However, a double-blind, randomized controlled trial study conducted on few selected patients from arsenic-affected West Bengal (India) regions with oral administration of DMSA suggested that DMSA was not effective in producing any clinical or biochemical benefits or any histopathological improvements of skin lesions [27]. Although DMSA is an effective drug for the treatment of metal intoxication, however, because of its hydrophilic and lipophobic properties, it is unable to pass through cell membranes [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative evaluation of three drugs reveals that DMPS is 28 times more effective than BAL in arsenic therapy in mice, and DMSA and DMPS are equally effective. Guha Majumder et al evaluated the efficacy of DMPS in a single blind placebo control trial of patients suffering from chronic arsenic poisoning in West Bengal, India 53) . DMPS was given in a 100 mg capsule dose 4 times a day for 7 d for four courses with a one-week drug free period between courses.…”
Section: Conventional Chelating Agents and Their Drawbacksmentioning
confidence: 99%